The role of government financial support and innovation adoption on the performance of SMEs in South Africa - Thapelo, Pulane (My University, 2020)
Small and Medium Enterprises (SMEs) are seen as a primary tool for driving economic performance in South Africa. However, SMEs’ higher failure rate remains to be one of the biggest obstacles in the SME sector in South Africa. There are number of challenges that SMEs are faced with due to their size, including lack of skills, lack of access to capital and their inability to incorporate innovation in their firms. The purpose of this research is to investigate the relationship between innovation adoption and SME performance, determine the role of government financial support on SME performance and SME innovation adoption. This study adopted a quantitative research method based on a positivist research paradigm to test the hypothesis generated. A sample size of 152 was collected from South African SMEs through self-administered questionnaires. Multiple regression was applied to test the relationships between dependent and independent variables. Evidence revealed that government financial assistance is essential for enhancing SME performance and encouraging innovation in small businesses.
A research report submitted, in partial fulfilment of the requirements for the degree of Master of Management in Entrepreneurship and New Venture Creation to the Faculty of Commerce, Law and Management, University of the Witwatersrand Johannesburg 2020
Keywords: Government financial support; Innovation adoption; SME performance; SDG-8: Decent work and economic growth